Restorative Injustice: A Study of Failed Implementation of Restorative Practices at an Urban High School - Cama, Paul Gerard (2019)
The restorative justice process utilizes various intervention strategies created by indigenous tribes throughout the world, as an alternative to procedural justice (Zehr, 2002). In modern education, restorative justice was incorporated into the public-school system, where it has evolved into a preemptive measure to combat punitive discipline policies that is often seen as both racially insensitive and detrimental to the learning of students. The purpose of this study was to examine the implementation process of a school based restorative justice program at an urban high school and focused on how these interventions were implemented, what resources were allocated, and how it was embedded within the school culture. A qualitative approach was chosen because the restorative justice process contains multiple variables, such as perceptions, feelings, ideas, personal ideology, and cultural factors. The sampling plan consisted of interviews, and field notes collected from a Colorado high school that was at the beginning stages of implementing a restorative justice program. Data was analyzed through the lenses of the district-based success criteria created by Anyon (2016) and Howard Zehr's (2002) conceptual pillars of restorative justice (Zehr, 2002). Findings indicated that implementation of restorative practices at the school site was procedural and technical rather than rooted in the theory and philosophical tenets of restorative justice. Several themes also emerged from the analysis of implementation, such as restorative practices seen as disciplinary tool by administration, the isolated and variable implementation of the process, and role specific ownership of the process. Recommendations for school administration and district employees are presented in this study to assist them in ways to improve their current implementation of restorative practices